Towering skyscrapers built on Malabar Hill overlooking Banganga Tank - Banganga by Ghosh, Ayan (2023)
Towering skyscrapers built on Malabar Hill overlook Banganga Tank. In the 18th century, the hill was densely forested and visited only by Hindu pilgrims and Malabari pirates. Later, in the 1880s, the British Governor shifted Raj Bhawan from Parel to Malabar Hill and the neighborhood has since been one of the most sought-after real estates in Mumbai.